PENERIMAAN DIRI TERHADAP AKTIVITAS PERAWATAN DIRI PASIEN DIABETES MELLITUS TIPE 2 - Susilawati, Ela; Muspita, Della; Effend, Dian Puspitasari; Febrianti, Hana (Jurnal Kesehatan Holistic, 2025)
Introduction, Diabetes Mellitus is one of the fastest growing global health emergencies today. A person with diabetes must depend on diabetes management therapy to overcome physical and psychological changes. Self-acceptance can improve patient behavior related to diet, health compliance, seeking information about the disease, improving lifestyle, and getting used to being active, and avoiding excessive emotions and stress. Objective, to determine the relationship between self-acceptance and self-care activities of Diabetes Mellitus patients. Method, Quantitative with a Cross-sectional approach. The design in the study is Analytical Correlation. Using the Acceptance of Illnes Scale questionnaire and The Summary of Diabetes Self Care Activities questionnaire. Research Results, It is known that the results of the study obtained good self-acceptance results of 34%, poor self-acceptance of 66%. Good self-care activities of 47.2%, poor self-care activities of 52.8%. Where the results of the Chi-Square statistical test showed that there was no relationship between self-acceptance and self-care activities with a P Value of 0.767> ? 0.05. Conclusion, Respondents with good self-acceptance will have 2x better self-care activities compared to respondents who have poor self-acceptance.